(untitled) (Revista Electrónica REDINE, 2018)
The growth of virtual education (EV) in Venezuelan universities, has taken shape changes in education and therefore the meanings of social actors involved in this type of education. This reality is the basis of this study, which was proposed to generate Educational Approaches to the on lines Courses in the Faculty of Health Sciences (DCS) Centroccidental University "Lisandro Alvarado" (UCLA), in relation to its conceptualization, teaching practice and axiology of the online courses. Moreover, for that, it was assumed as basis epistemic social constructionism and qualitative methodological approach, interpretive paradigm and the phenomenological-hermeneutical method. The techniques and instruments used for data collection were dialogic depth interviews and online. The review of the information was using the method Colaizzi (1976), follower of Husserl, allowing addressing each of the witnesses and then go setting categories (3) with their respective subcategories (14). Educational approaches on the meanings of teachers regarding the conceptualization, teaching practice and axiology of Virtual Education through online courses generated. Also intersubjectivity between researcher and teachers allowed to appreciate the importance of incorporating ICTs or networks to facilitate the educational process in the virtual mode, and achieve new meaning embedded assumptions of social actors in that mode. It was believed that only in this way, the education from the virtual education process achieved its purpose.